Droits de l'homme : histoire et modernité - Gorbacheva, Victoria (Chisinau (Moldova) : Editions Notre Savoir/ScienciScripts, 2021)
Micheline Ishay recounts the dramatic struggle for human rights across the ages in a book that brilliantly synthesizes historical and intellectual developments from the Mesopotamian Codes of Hammurabi to today's era of globalization. As she chronicles the clash of social movements, ideas, and armies that have played a part in this struggle, Ishay illustrates how the history of human rights has evolved from one era to the next through texts, cultural traditions, and creative expression. Writing with verve and extraordinary range, she develops a framework for understanding contemporary issues from the debate over globalization to the intervention in Kosovo to the climate for human rights after September 11, 2001. The only comprehensive history of human rights available, the book will be essential reading for anyone concerned with humankind's quest for justice and dignity.
Keywords: Human rights -- History; Droits de l'homme (Droit international) -- Histoire